(untitled) (Conference Zone, 2022)
In the decree of the president of the Republic of Uzbekistan dated 08.10.2019 № PF-5847 on approval of the concept of development of the higher education system of the Republic of Uzbekistan up to 2030: "determination of the priority directions of systematic reform of higher education in the Republic of Uzbekistan, raising the process of training of highly qualified personnel, priority tasks of" development of social sphere and economic sectors based on advanced educational technologies" are defined. In this article, on the basis of dual education, opinions and comments are made about the improvement of practical compensation of future teachers.